Alcohol Consumption and Current Situation of Drinking Risk Level Among University Students in Mandalay Region - Aung, Yadanar; Ou, Yin Thet Nu; Wan, Nanda Myo Aung; Nyan, Bo Bo; Phyo, Aung Pyae; Win, Le Le (Yayasan Aliansi Cendekiawan Indonesia Thailand (Indonesian Scholars' Alliance), 2019)
Background: In Myanmar, alcohol consump on among university students had been recognized as a major pub- lic health concern. A cross-sec onal study was done to inves gate drinking alcohol and risk level assessment using the Alcohol Use Disorder Iden fica on Test (AUDIT) and examined the reasons of alcohol uses and types of beverage preference consumed. Methods: The two universi es from three districts in Mandalay region were randomly selected, from which 976 students (stra fied by academic year and sex) were contributed in self-administered ques onnaire. Results: The mean age at first drinking alcohol among the par cipants was 16.36±0.15 years with range of 16 to 19 years. The drinking risk level assessment using the AUDIT test, nearly half of the par cipants 48.7% were abstainers and 86 (8.8%) were high risk drinkers while 28 (2.9%) had alcohol dependency. Among those, 57.8% had experiences of alcohol drinking and the favorite beverage of the university students who drink alcohol was beer. Binary logis c regression analysis indicated that gender, smoking habit and living situa on for drinking were significant predictors of alcohol consump on among university students. The results found out that living separately with parents and smoking habits were important factors for drinking alcohol with sta s cally signifi- cant at 95% confidence level. Conclusion: It provided evidence-based findings for knowing the alcohol consump on risk level among univer- sity students to prevent social depriva on and health risk behaviors. Findings from this study indicate a need for law governing, strictly prohibits the sale of alcohol directly or indirectly to those under the age of eighteen years. The alcohol interven on program can be helpful in modifying behaviors change communica on in health promo on of university students.